URSUS SPELAEUS FROM GROTTA SOPRA FONTANA MARELLA, CAMPO DEI FIORI MASSIF (VARESE, ITALY): MORPHOMETRY AND PALEOECOLOGY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
The paleontological study on cave bear remains from the Grotta Sopra Fontana Marella (Campo dei Fiori massif, Varese, Italy) is here presented. The cave bear material was collected in three different levels of the cave stratigraphical sequence which are assigned to Late Pleistocene by radiometric ages and aminoacid racemization analysis. This deposit gives us the rare opportunity to compare cave bear remains that lived in the same geographical areas but at different time intervals. Cave bears from the oldest level (FM4) had a peculiar mandible morphology and a smaller body size than cave bears from the uppermost levels (FM1 and FM2). We propose that this change in body size is related to a paleoclimatic trend from FM4 towards a colder phase (FM1 and FM2), the latter corresponding to the last maximum expansion of glaciers in the Italian Alps. Morphometric analysis of bones and teeth allowed to determine minimum number of individuals, class ages and sex ratio for each cave bear fossil assemblage.